Protective LRRK2 R1398H Variant Enhances GTPase and Wnt Signaling Activity - Nixon-Abell, Jonathon; Berwick, Daniel C.; Grannó, Simone; Spain, Victoria A.; Blackstone, Craig; Harvey, Kirsten (Frontiers in Molecular Neuroscience, 2016)
Mutations in LRRK2 are a common cause of familial and idiopathic Parkinson’s disease (PD). Recently, the LRRK2 GTPase domain R1398H variant was suggested in genetic studies to confer protection against this condition but mechanistic data supporting this observation is lacking. Here, we present evidence that R1398H affects GTPase function, axon outgrowth and Wnt signalling in a manner opposite to pathogenic LRRK2 mutations. LRRK2 R1398H GTPase domain dimerization and GTP hydrolysis were increased whereas GTP binding was decreased leading to a decrease in active GTP-bound LRRK2. This protective variant also increased axon length of primary cortical neurons in comparison to wild-type LRRK2, whereas the R1441G LRRK2 pathogenic mutant decreased axon outgrowth. Importantly, R1398H enhanced the stimulatory effect of LRRK2 on canonical Wnt signalling whereas the G2385R risk variant, in accordance with all previously tested pathogenic LRRK2 mutants, had the opposite effect. Molecular modelling placed R1398H in close proximity to PD-causing mutations suggesting that this protective LRRK2 variant, like familial mutations, affects intramolecular RocCOR domain interactions. Thus, our data suggest that R1398H LRRK2 is a bona fide protective variant. The opposite effects of protective versus PD associated LRRK2 variants on GTPase function and canonical Wnt signalling activity also suggests that regulation of these two basic signalling mechanisms is important for neuronal function. We conclude that LRRK2 mediated Wnt signalling and GTPase function are fundamental in conferring disease susceptibility with clear implications for therapeutic target identification.